SOCIO-SCIENTIFIC STUDY: RELATIONSHIP OF STUDENTS' SOCIAL INTERACTIONS WITH NATURAL SCIENCES LEARNING OUTCOMES - Mohammad Archi Maulyda; Muhammad Erfan (JURNAL SPEKTRA, 2021)
Social interactions that occur between individuals in natural sciences are called socio-scientific. Socio-scientific norms are rules derived from mathematical values brought into the social context.  norms are seen as being able to increase students' understanding. The main focus in this research are, (1) Analyzing social content in elementary natural sciences learning courses; (2) Describe the process of social interaction on research subjects; and (3) describe the relationship between social interaction and natural sciences learning outcomes. This type of research is quantitative with a descriptive approach. Study subjects was 100 prospective elementary school teachers. Data collection techniques was using survey methods and analysis of student’s final exam in natural sciences test. Data analysis uses simple linear regression analysis. From the research, the results are obtained: (1) Mathematical content in the lecture process has been raised by the lecturer. The lecture system in the form of group discussions can improve students' communication, courage and collaboration skills. (2) The description of students' social interactions can be modeled. Social interaction models show social interaction can be in the form of associative and dissociative. (3) There is a relationship between social interaction with learning outcomes in natural sciences. The relationship is quite strong, and social interaction influences student natural sciences learning outcomes